Reduced environmental footprint through novel food production technologies: Four case studies from Finland - Leino, Katri; Silvenius, Frans; Lehtilä, Anniina; Katajajuuri, Juha-Matti (Elsevier, 2025)
New ways to reduce the climate impact and land occupation of agriculture and food production are needed. This study assessed the potential of four new food production solutions to mitigate the climate impact at the national level in Finland by partly replacing conventional food production solutions. The climate mitigation potential of reforestation of saved land was also assessed. The new production solutions assessed represent cellular agriculture and controlled environment agriculture (CEA). The climate impact and land occupation were assessed for the four new production solutions and for four conventional production solutions using life cycle assessment (LCA). Land use and land use change (LULUC) emissions were systematically included in the LCA. The LCA results were scaled up to the national level with estimated production amounts for Finland. The results showed that these four new solutions can have an impact at the national level when partly replacing conventional solutions. There is mitigation potential in reforestation of the saved land, but the main impact was achieved by replacing conventional production. Cellular agriculture and CEA can provide significant reductions in climate impact, but for CEA reductions in the climate impact depend on the energy sources used. Using low-carbon energy sources ensures that reductions in land occupation can be achieved, as bio-based renewable energy causes large land occupation. The results highlight the importance of considering LULUC emissions in LCAs of conventional agricultural products, especially in areas with organic soils. Decreasing cultivation on organic soils has a high climate impact mitigation potential for conventional food production.
Keywords: life cycle assessment; climate impact; land occupation; novel food production; cellular agriculture; controlled environment agriculture